Influence of the balance of the intertropical front on seasonal variations of the isotopic composition in rainfall at Kisiba Masoko (Rungwe Volcanic Province, SW, Tanzania). Issue 4 (4th July 2018) - Nivet, Fantine; Bergonzini, Laurent; Mathé, Pierre-Etienne; Noret, Aurélie; Monvoisin, Gaël; Majule, Amos; Williamson, David
ABSTRACT: Tropical rainfall isotopic composition results from complex processes. The climatological and environmental variability in East Africa increases this complexity. Long rainfall isotope datasets are needed to fill the lack of observations in this region. At Kisiba Masoko, Tanzania, rainfall and rain isotopic composition have been monitored during 6 years. Mean year profiles allow to analyse the seasonal variations. The mean annual rainfall is 2099 mm with a rain-weighted mean composition of −3.2 ‰ for δ 18 O and −11.7 ‰ for δ 2 H. The results are consistent with available data although they present their own specificity. Thus, if the local meteoric water line is δ 2 H = 8.6 δ 18 O + 14.8, two seasonal lines are observed. The seasonality of the isotopic composition in rain and deuterium excess has been compared with precipitating air masses backtracking trajectories to characterize a simple scheme of vapour histories. The three major oceanic sources have two moisture signatures with their own trajectory histories: one originated from the tropical Indian Ocean at the beginning of the rainy season and one from the Austral Ocean at its end. The presented isotopic seasonality depends on the balance of the intertropical front and provides a useful dataset to improve the knowledge about local processes.